Evaluation of sunflower hybrids for their suitability in North Eastern Hill Regions of India: EVALUATION OF SUNFLOWER HYBRIDS FOR SUITABILITY IN NORTH EASTERN HILL REGIONS OF INDIA - A AZIZ QURESHI; R K SINGH; D SEN; L K BAISHYA; A P SINGH; A VISHNUVARDHAN REDDY; R K AVASTHE; D PATI (Journal of Oilseeds Research, 2018)
Five sunflower hybrids and a variety were evaluated in four different centres of North Eastern Hill (NEH) regionsto study their suitability in terms of growth, yield and oil content to tap the potential rice fallow areas in NEH regions (Jharnapani, Medziphema, Tadong, and Lembucherra). Uniform layout was adopted at four locations to conduct field trials with RBD design. The soils of the region except Lembucherra were found to be acidic (ranged between 4.6 and 5.7 pH) and therefore requires regular lime application for obtaining high seed yields ofsunflower. The location Tadong was on high altitude (1300 m MSL) and recorded less number of average sunshine hours (2.5hours/day) during the sunflower crop period was responsible for lanky growth of sunflower with low oil content. However, Lembucherra was highly suitable for growing sunflower as weather conditions were highly favourable. Further, assessment of various growth and yield parameters it was found that average yield ofsunflower in Tadong location was the highest (1814 kg/ha) but had low average oil content (28.6%) and attained average maturity in 135 days. While Lembucherra centre recorded seed yield of 1532 kg/ha with average oil content of 37.1 per cent and found to complete crop cycle at the earliest over other centres by attaining maturity on an average in 113 days. Among all the hybrids, DRSH-1 showed highest oil content in all the locations and mean value across the centres was 39.6 per cent.